Representasi Sistem Nilai dari Istilah-istilah dalam Tradisi Betian Masyarakat Sasak : Kajian Linguistik Antropologi - Erny Yuliansari; Burhanuddin Burhanuddin; Johan Mahyudi; Aswandikari Aswandikari; Saharudin Saharudin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The betian tradition is a traditional activity carried out by the Sasak people during the process of waiting for pre-pregnancy, pregnancy, and post-pregnancy. This tradition is a form of gratitude to God and a prayer for the safety of the mother-to-be, pregnant woman, fetus, and newborn baby. The purpose of this research is to examine the lingual forms used in the Betian tradition and to examine the value systems represented in these linguistic forms. This research is a qualitative-descriptive research. Data was collected using speech (interview) and observation methods, while data analysis used principles in anthropological linguistics, namely intralingual and extralingual matching methods. The results of this study show that the betian tradition is divided into 3 semantic domains, namely pre-pregnant (ngantih), pregnant (nebon), and post-pregnancy (nganak). Each semantic domain has lingual forms that are reflected in the naming of customary processions during the Betian tradition. The lingual form consisting of verbs, nouns, and adjectives represents a value system that is reflected in cultural behavior, such as joint prayer, mutual cooperation, celebrations, counting good days, and cultural inheritance.